2013
DOI: 10.1097/iae.0b013e318280769c
|View full text |Cite
|
Sign up to set email alerts
|

Half-Fluence Photodynamic Therapy in Chronic Central Serous Chorioretinopathy

Abstract: ICGA-guided half-fluence PDT with verteporfin is effective in treating chronic symptomatic central serous chorioretinopathy with choroidal hyperpermeability in ICGA, resulting in both visual improvement and reduction of central foveal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 25 publications
0
43
0
1
Order By: Relevance
“…[1][2][3][15][16][17][18][19][20][21] In a retrospective study, Mudvari et al 29 found that none of the 340 consecutive CSCR patients developed CNV during an approximate 4-year follow-up period (mean of 49 months). However, Spaide et al 30 reported that older patients with CSCR had a lower VA, and were more likely to have diffuse retinal pigment epitheliopathy and secondary CNV than their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][15][16][17][18][19][20][21] In a retrospective study, Mudvari et al 29 found that none of the 340 consecutive CSCR patients developed CNV during an approximate 4-year follow-up period (mean of 49 months). However, Spaide et al 30 reported that older patients with CSCR had a lower VA, and were more likely to have diffuse retinal pigment epitheliopathy and secondary CNV than their younger counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, experience due to previous studies conducted at our tertiary center on acute and chronic CSCR enabled us to follow a PDT regimen, using half-dose fluence rate (25 J/cm 2 ), while not changing the dose of verteporfin (6 mg/m 2 ). [16][17][18] Selecting an appropriate fluence rate helps avoiding collateral damage as atrophy of the RPE, choroidal ischemia, and development of secondary CNV due to less choriocapillaris damage. [18][19][20] Said avoidance of negative treatment effect of RPE's metabolic activity was shown in a study of Hagen et al, 36 where the focus was set on RPE alterations in eyes with acute CSCR treated with half-fluence PDT observed via shortwavelength fundus autofluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,[48][49][50][51][52] Reduced fluence vPDT therapy uses a vPDT laser fluence of 25 J/cm 2 (300 mW/cm 2 for 83 s). 14,15,53,54 There is limited evidence to compare these different vPDT protocols for CSC in the absence of randomised controlled trials. 44,[55][56][57][58] The current approach to management of CSC is largely empirical.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%